A precautionary tale when describing species in a world of invaders: Morphology, coloration and genetics demonstrate that Lysmata rauli is not a new species endemic to Brazil but a junior synonym of the Indo-Pacific L. vittata - Soledade, Guidomar Oliveira; Baeza, Juan Antonio; Boehs, Guisla; Simões, Sabrina Morilhas [UNESP]; Santos, Patricia Souza; Costa, Rogério Caetano da [UNESP]; Almeida, Alexandre Oliveira (Oxford University Press (OUP), 2013)
The objective of this study was to investigate morphological variation in traits of systematic relevance and the phylogenetic position, ecology, and reproductive biology of the shrimp Lysmata rauli Laubenheimer and Rhyne, 2010 (Caridea: Hippolytidae), described based only on a single specimen collected in Salvador, Bahia, Brazil. We analyzed a total of 89 specimens from Camamu Bay, Bahia (n = 88) and from S3o Vicente estuary, São Paulo (n = 1). Considerable morphological variation was detected in the rostral spine series, number of segments on the carpus and merus of pereiopod 2, number of spiniform setae on the ventrolateral margin of merus and on the ventral margin of propodus of pereiopods 3-5. Importantly, L rauli can be distinguished neither using morphology, nor coloration from the Indo-Pacific L. vittata (Stimpson, 1860). Furthermore, molecular phylogenetic analyses (using the 16S mt DNA fragment) did not reveal any considerable genetic dissimilarities between L rauli and L vittata. Thus, our results clearly indicate that L rauli is not a new species but a junior synonym of L vittata. The high density observed within the structures of oyster farming indicates that the invasive L vittata lives in crowds in Brazil. The studied population was composed of males, hermaphrodites, and transitional individuals (having characteristics of males and hermaphrodites). The above information suggests that L rauli is a protandric simultaneous hermaphrodite, as it has been observed in all species of Lysmata that have been investigated. Lysmata vittata has invaded the southwestern Atlantic and is present in Bahia, Rio de Janeiro and S3o Paulo, Brazil. © The Crustacean Society, 2013. Published by Brill NV, Leiden.
Keywords: Alien species; Hermaphroditism; Lysmata; Morphology; Population structure